تطبيق طريقة تدريس الأقران في تعليم القواعد النحوية في المدرسة الثانوية الإسلامية الحكومية الخاصة جمبير للسنة الدراسية ٢٠٢٣ / ٢٠٢٤ م (MANPK) - Hasanah, Siti Maulidatul; Nurchayati, Siti (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2026)
Peer tutoring is a method that involves students helping each other learn academic material by reviewing and reinforcing key concepts. This method has been implemented as one of the teaching strategies for Arabic grammar (nahwu) in the MANPK Jember program. Teaching the Arabic language, especially Arabic grammar is one of the subjects that receives great attention at this school. One of the reasons is that the textbooks used in Islamic religious studies are written in Arabic. The research employs a qualitative approach with a case study (field research) design. Data were collected through observation, interviews, and documentation. The data analysis in this study follows the framework proposed by Miles, Huberman, and Saldana, which includes data condensation, data display, and verification. The validity of the data was ensured through triangulation. The results of the research show that the peer tutoring method was applied in teaching Arabic grammar (nahwu) in the MANPK Jember program, both during the learning process at the boarding school and in large classroom settings.The implementation consists of four stages: 1) The teacher explains the Arabic grammar materials to the students when they are in the 10th grade, first semester, for about five to six months, 2) The teacher divides the students into several groups, 3) The students explain the material to their peers within their groups, 4) The teacher conducts an evaluation. The problems encountered include: 1) Many students have difficulty maintaining concentration during the learning process, 2) Some students feel bored because this method is used daily to teach Arabic grammar rules, 3) Some students who act as tutors do not perform their roles effectively.